Celebrating (or Not) The Russian Revolution. (October 2017) - Fitzpatrick, Sheila
The Russian Revolution has long been a subject of controversy among Russian/Soviet historians, both in the West and Russia/the Soviet Union. Now that the centenary has arrived, conferences are being held widely in Europe and the Americas, but less widely in the Russian Federation. For Putin's regime, with its ambiguous relationship to the Soviet past, the centenary of the Russian Revolution is something of an embarrassment. An attempt to celebrate under the slogan of 'reconciliation' may or may not succeed.